2022
DOI: 10.11152/mu-3303
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound versus physical examination in predicting disease flare in children with juvenile idiopathic arthritis: a systematic literature review and qualitative synthesis

Abstract: In this systematic review we analyzed the published articles related to the predictive value for flare of subclinical synovitis assessed by ultrasound (US) in juvenile idiopathic arthritis (JIA). Medline, Embase and Cochrane databases were searched from 1990 to 2020 by two authors, using PICO methodology. The study is built and reported according to PRISMA guidelines. Searches identified four articles comprising a total of 187 JIA patients in clinical remission from at least 3 months. Two of the articles found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Ultrasound has been found to be a valid tool for the detection of synovitis in JIA, some authors have found a prevalence of low to moderate subclinical synovitis by ultrasound, particularly in small joints. However, the prognostic significance of such subclinical synovitis remains to be determined [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has been found to be a valid tool for the detection of synovitis in JIA, some authors have found a prevalence of low to moderate subclinical synovitis by ultrasound, particularly in small joints. However, the prognostic significance of such subclinical synovitis remains to be determined [4,11,12].…”
Section: Introductionmentioning
confidence: 99%